2022
DOI: 10.3390/v14010107
|View full text |Cite
|
Sign up to set email alerts
|

Short ‘1.2× Genome’ Infectious Clone Initiates Kolmiovirid Replication in Boa constrictor Cells

Abstract: Human hepatitis D virus (HDV) depends on hepatitis B virus co-infection and its glycoproteins for infectious particle formation. HDV was the sole known deltavirus for decades and believed to be a human-only pathogen. However, since 2018, several groups reported finding HDV-like agents from various hosts but without co-infecting hepadnaviruses. In vitro systems enabling helper virus-independent replication are key for studying the newly discovered deltaviruses. Others and we have successfully used constructs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…While SDeV produces a single form of SDAg in cultured snake cells (Fig. 1E) and in infected snakes 13,14 , we observed two forms of the SDAg in human Huh7.5 and HEK293T cells (Fig. 1C).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…While SDeV produces a single form of SDAg in cultured snake cells (Fig. 1E) and in infected snakes 13,14 , we observed two forms of the SDAg in human Huh7.5 and HEK293T cells (Fig. 1C).…”
Section: Discussionmentioning
confidence: 81%
“…The findings led to the creation of the novel realm Ribozyviria with the family Kolmioviridae to host the genus Deltavirus and seven other genera 16 . As only a minority of the studies on novel kolmiovirids made efforts towards molecular characterization of their replication 9,11,14 , our understanding of the kolmiovirid biology relies on the seminal research performed on HDV. Importantly, the cross-species transmission potential of kolmiovirids 10 coupled to their ability to form infectious particles with envelope proteins of a variety of helper viruses 13,32 raises an important question: can these minimal RNA viruses replicate in any animal cell they access?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These discoveries indicated that this new viral family is far more diverse and widespread amongst the animal kingdom than originally thought. Evidence that HDVlike viruses found in snakes [13,14], rodents [9,11] and birds [11] are able to replicate and the recent identification of thousands of sequences similar to deltaviruses in metatranscriptomes [12,15] led to the establishment of a novel realm, Ribozyviria, with a single family, Kolmioviridae, that includes the genus Deltavirus as well as seven other novel genera of kolmiovirids [16]. Because other kolmiovirids were only recently discovered, most of our knowledge of the biology of these agents stems from research on HDV [17].…”
Section: Introductionmentioning
confidence: 99%